Use of mobile applications as a strategy to support family members in the care of newborns: a scoping review protocol - Araujo, Juliane Pagliari; Gallo, Adriana Martins; de Lima Parada, Cristina Maria Garcia [UNESP]; Marcon, Sonia Silva; Ferrari, Rosângela Aparecida Pimenta; da Fonseca Pinto, Keli Regiane Tomeleri; Zani, Adriana Valongo (Escola de Enfoermagem Aurora de Afonso Costa, 2023)
Objective: To map and describe the studies available in the literature and online stores on mobile applications to support family members of newborns. Method: This is a scoping review protocol, prepared following the recommendations of the Joanna Briggs Institute and the items of the PRISMA Extension for Scoping Reviews (PRISMA-ScR): Checklist and Explanation. The search will be carried out in two stages: 1 - in PubMed, CINAHL, Web of Science, Scopus, LILACS, Embase, Cochrane Library, Google Scholar, and Scielo databases, and in the VHL, the Latin American Theses and Dissertations Portal, and the catalog of theses and dissertations of the Coordination of Improvement of Higher Education Personnel; 2 - in the online stores of Android and iOS operating systems, through the independent use of the term “newborn”. The protocol will guide the development of the scoping review for the description and mapping of mobile applications to support family members of newborns.
Utilização de aplicativos móveis como estratégia de apoio a familiares no cuidado a recémnascidos: protocolo scoping review
Keywords: Family; Mobile Applications; Newborn Infant